Two Cases of Persistent Complex Bereavement Disorder Diagnosed in the Acute Inpatient Unit. (2nd April 2020) - Olaolu, Olalekan; Tumenta, Terrence; Adeyemo, Samuel; Popoola, Olusegun; Oladeji, Oluwatoyin; Olupona, Tolu
Abstract : Pathological grief has been noted to have considerable adverse effects on affected individuals. In the DSM-5, the diagnosis of complicated grief is included under conditions for further study as Persistent Complex Bereavement Disorder (PCBD). PCBD can be easily missed because it is a relatively new and developing diagnosis. It can also be overlooked when it is comorbid with more common psychiatric disorders. We present 2 patients with PCBD diagnosed in the inpatient unit, while the patients were admitted for comorbid disorders. PCBD contributed immensely to both patients' suffering and decline in functioning. This report highlights the presentation, diagnoses, and management of these patients. We theorize that paying attention to separation distress, reactive distress to loss, and identity disruption in individuals who have been bereaved for over 12 months will enhance treatment specificity and lead to better patient outcomes.